UPAYA PENGEMBANGAN KELOMPOK USAHA KERAJINAN ‘BATIK RIAU’ DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI KOTA PEKANBARU - Hidayat Marzuki; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Batik is widely known in Indonesia which is often associated with handicrafts and is also not infrequently included in the category of clothing industry. Batik industry, in its development in Indonesia dominated by small and medium scale business. In the context of the economic empowerment of the people, the policy support of the Small and Medium Industry is set forth in Law No. 3 of 2014 on Perindustian, namely central and regional government to empower small and medium industries (IKM) competitiveness, significant role in industrial structure, In poverty alleviation, by formulating policies.The method used in this study was conducted by qualitative approach with descriptive method, with data collection techniques including observation, interview, documentation study related to research objectives. Instrument in this study refers to the theory that Widjaja (2003) describes that empowering a community group to support the development of community potency in running the business through increasing role, productivity and efficiency by improving 4 (four) access that is, access to resources, Technology, access to markets, access to financing sources.The result of the research shows that the effort of handicraft business group 'Batik Riau' in community empowerment in Pekanbaru city has not run optimally. Access to capital resources in an effort to develop creative industries batik craft 'Creative House Cempaka' in Pekanbaru City still depend on the source of financing and funds through CSR program PT. Chevron Pacific, and very limited sales of batik handicrafts. Access to markets is still limited in the scope of 'Creative House of Cempaka' stores with simple marketing information technology (word of mouth) has not utilized access to technological developments. Financing access to financial institutions still faces administrative requirements that must be met, such as grants.Keywords: Empowerment, Batik, Small and Medium Industry, Business Capital.